Irradiance sensor array data analysis - Raja Rajan, Rajendran (2016)
Singapore’s tropical climate, proximity to the equator and large supply of sunshine has opened up the possibility of harnessing solar energy as an alternative source of clean energy for the country. However, the island country also experiences frequent intermittent cloud movements throughout most days. This prevents solar PV installations from being able to harness maximum solar energy throughout the day, thereby limiting grid penetration capabilities of solar energy throughout the country. The studies done in this paper extended several works done by researchers in other areas of the globe to quantify the local solar irradiance variability using various metrics such as Coefficient of Variability, Variability Index and solar irradiance ramps along the dimensions of time and space. The results of studies have shown that for any given day, the variability of the solar irradiance at various hours of the day can vary as much as the irradiance itself. Also, when multiple readings of irradiance data is obtained over a larger surface area, the overall variability for the area drops by a significant percentage, and the solar irradiance ramp distributions even out towards lower magnitudes with longer durations. From these studies, it can be noted that following the trends of the solar irradiance variability, PV systems have a high possibility of producing less-varied, more stable power output if the power generated was aggregated from multiple sources over a larger land area.